Highly Sensitive Tungsten Oxide Thin Film‐Based Field‐Effect Transistor for Real‐Time Monitoring of Dissolved Ammonia in Human Plasma. Issue 19 (31st May 2022) - Sharma, Sumit; Moudgil, Akshay; Singh, Sanjay; Das, Samaresh; Mishra, Prashant
Abstract: Field‐effect transistors (FETs) based on metal‐oxide thin film have the advantage of excellent sensitivity, fast response, miniaturized size, and compatibility with bio‐analytes. In this work, a highly responsive FET biosensor is fabricated based on tungsten trioxide (WO3 ) thin film to detect the physiological concentration of total ammonia (ammonium NH4 + and NH3 ) in human body fluids. The elevated level of ammonia in the body fluids indicates damage or improper functioning of organs mainly the liver. Thus, real‐time monitoring of ammonia concentration in human body fluid acts as a prognostic marker for liver disorders. The fabricated FET device shows reliable and accurate results for ammonia sensing with the highest response of 498 at 100 µM and a limit of detection of 6 µM. This device measures the ammonia in body fluid faster than available techniques and shows a high response towards ammonia in commercially available human plasma. This is also capable of real‐time detection of very low concentrations of ammonia (2 µM) with a wide range from 2 to 100 µM. Also, the prospect of the device's batch fabrication is demonstrated with consistent and high stability performance. This study demonstrates a unique and stable sensing platform, capable of direct detection of ammonia concentration in human plasma for point of care applications. Abstract : A unique and stable sensing platform based on a WO3 thin‐film transistor, capable of directly detecting the rising ammonia level in plasma is demonstrated. The fabricated field‐effect transistor device shows real‐time detection of dissolved ammonia as a prognostic marker for liver disorders in human plasma with the highest response of 498 at 100 µM and a limit of detection of 6 µM.